Temperature and soil moisture monitoring of celery trials and compost piles at a farm in Fairbanks, Alaska from May 2022 to March 2023 ... - Ward Jones, Melissa; Gannon, Glenna; Jones, Benjamin (NSF Arctic Data Center, 2024)
The Permafrost Grown project (NSF RISE Award # 2126965) is co-producing knowledge with farmers in Alaska (Tanana Valley and Bethel) to investigate the interactions and feedbacks between permafrost and agriculture. Additional project objectives include understanding legacy effects over a 120-year cultivation history in the Tanana Valley, evaluating the socio-economic effects of permafrost-agriculture interactions and provide decision making tools for farmers and finally to utilize education and outreach activities to share knowledge with the farmers and the public. The project focuses on in-the-ground farming in a range of cultivation types including crops, peonies and livestock. The project is funded through the National Science Foundation's (NSF) Navigating the New Arctic Initiative. Data was collected at a small (less than one acre) farm that grows diverse crops. This farm has been impacted by subsidence from thawing ice-rich permafrost. The goal of the celery trials was to compare celery grown in areas ...